2015
DOI: 10.1038/ki.2015.150
|View full text |Cite
|
Sign up to set email alerts
|

Renal systems biology of patients with systemic inflammatory response syndrome

Abstract: A systems biology approach was used to comprehensively examine the impact of renal disease and hemodialysis (HD) on patient response during critical illness. To achieve this we examined the metabolome, proteome, and transcriptome of 150 patients with critical illness, stratified by renal function. Quantification of plasma metabolites indicated greater change as renal function declined, with the greatest derangements in patients receiving chronic HD. Specifically, 6 uremic retention molecules, 17 other protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 64 publications
(95 reference statements)
1
49
0
Order By: Relevance
“…Metabolomic changes have also been demonstrated to affect immune function in sepsis and renal dysfunction [38, 39]. It was found that patients that presented to the emergency department with sepsis and chronic renal failure had a pan-transcriptomic decrease in expression in white blood cells isolated from septic patients enrolled in the emergency department.…”
Section: Molecular Changes To the Innate And Adaptive Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomic changes have also been demonstrated to affect immune function in sepsis and renal dysfunction [38, 39]. It was found that patients that presented to the emergency department with sepsis and chronic renal failure had a pan-transcriptomic decrease in expression in white blood cells isolated from septic patients enrolled in the emergency department.…”
Section: Molecular Changes To the Innate And Adaptive Immune Responsementioning
confidence: 99%
“…It was found that patients that presented to the emergency department with sepsis and chronic renal failure had a pan-transcriptomic decrease in expression in white blood cells isolated from septic patients enrolled in the emergency department. Two metabolites allantoin and 4-pyridone-3-carboxamide (4PY) highly correlated with the majority of genes that were decreased due to chronic renal failure in sepsis patients [39]. It was speculated that 4PY, an endogenous inhibitor of poly(ADP-ribose) polymerase 1 (PARP1), could affect transcription in leukocytes.…”
Section: Molecular Changes To the Innate And Adaptive Immune Responsementioning
confidence: 99%
“…While it is known that sepsis contributes to AKI, the frequency with which sepsis develops as a consequence of AKI is currently being investigated and has been reported in several adult studies [1419, 43]. The investigators reported that 45% of non-survivors developed sepsis after the development of contrast-induced AKI [14].…”
Section: Discussionmentioning
confidence: 99%
“…A personalized medicine approach may have the best chance of identifying specific strategies for such a diverse patient population. A systems biology approach could complement the use of biomarkers to stratify patients, aid in prognosis, and help identify subsets of patients who may benefit or be harmed by therapy (Tsalik et al, 2015). However, the costs are high, and it is too early to know whether knowledge of the blood metabolome, proteome, and transcriptome could really direct therapy.…”
Section: Personalized Medicinementioning
confidence: 99%